A huge hepatic angiomyolipoma with growth during 5 years of follow-up. Issue 9 (25th September 2020) - Machida, Michio; Sugo, Hiroyuki; Watanobe, Ikuo
Abstract: A 45-year-old woman was referred to our hospital with a huge liver tumor that had been diagnosed as a hepatic angiomyolipoma (HAML) 5 years previously. At the time of referral, it had enlarged from 12 to 20 cm within the previous 5 years and become symptomatic. Enhanced computed tomography revealed a very large, well-defined, low-density mass occupying the entire right lobe of the liver. The patient underwent right hemi-hepatectomy. The resected specimen weighed 1620 g and measured 20 × 14 × 8 cm. The pathological diagnosis was confirmed as benign HAML. The estimated growth rate of this tumor was 44% per year with a doubling time of 826 days. Although the majority of HAMLs are stable lesions, resection should perhaps be considered when the tumor is known to be growing and exceeds 6 cm in diameter, even if it has been diagnosed as benign.